Population study of pupillary unrest in ambient light - McKay, Rachel Eshima; Kohn, Michael; Schwartz, Elliot; Larson, Merlin D. (Autonomic neuroscience, 2024)
Pupillary unrest in ambient light (PUAL) describes the fluctuation of pupil diameter observed in normal, awake subjects under typical levels of indoor light. PUAL becomes low to absent in young healthy subjects during opioid intoxication. We sought to determine the age-related distribution of PUAL values in a random sample of ambulatory participants. Subjects ≥18 years of age were recruited. All were identified by age range (18–29, 30–49, 50–69, and ≥70), and surveyed for diabetes, beta-blocker use, and prior 24-hour opioid use. Relationship between mean PUAL, age group, comorbidity and opioid use were examined by Kruskal Wallis test, and PUAL and was modeled using stepwise multilevel linear regression, including diabetes, beta blocker use, prior 24-hour opioid use, autonomic dysfunction, and pupil diameter as fixed effects and subject as random effect. Among 150 subjects, 17 reported diabetes, 12 reported beta-blocker use, 14 reported prior 24-hour opioid use, and 120 reported no comorbid conditions. PUAL declined in higher age categories (by 0.0307, P < 0.001), with diabetes (by 0.0481, P = 0.025), and with beta-blocker use (by 0.0616, P = 0.005). Opioid related PUAL decline was observed, but statistical significance varied by model. Among healthy subjects, no PUAL value fell within range indicating high likelihood of opioid toxicity based on previous data from healthy subjects undergoing opioid infusion. PUAL declined in higher age groups, diabetes and beta-blocker use, conditions associated with impaired autonomic function, and with opioid use but significance varied depending on the chosen model.